Socio‐economic differences in cardiovascular disease risk factor prevalence in people with type 2 diabetes in Scotland: a cross‐sectional study. Issue 8 (3rd April 2020) - Whittaker, E.; Read, S. H.; Colhoun, H. M.; Lindsay, R. S.; McGurnaghan, S.; McKnight, J. A.; Sattar, N.; Wild, S. H.
Abstract: Aim: To describe the association between socio‐economic status and prevalence of key cardiovascular risk factors in people with type 2 diabetes in Scotland. Methods: A cross‐sectional study of 264 011 people with type 2 diabetes in Scotland in 2016 identified from the population‐based diabetes register. Socio‐economic status was defined using quintiles of the area‐based Scottish Index of Multiple Deprivation (SIMD) with quintile (Q)1 and Q5 used to identify the most‐ and least‐deprived fifths of the population, respectively. Logistic regression models adjusted for age, sex, health board, history of cardiovascular disease and duration of diabetes were used to estimate odds ratios (ORs) for Q1 compared with Q5 for each risk factor. Results: The mean (sd ) age of the study population was 66.7 (12.8) years, 56% were men, 24% were in Q1 and 15% were in Q5. Crude prevalence in Q1/Q5 was 24%/8.8% for smoking, 62%/49% for BMI ≥ 30 kg/m 2, 44%/40% for HbA1c ≥ 58 mmol/mol (7.5%), 31%/31% for systolic blood pressure (SBP) ≥ 140 mmHg, and 24%/25% for total cholesterol ≥ 5 mmol/l, respectively. ORs [95% confidence intervals (CI)] were 3.08 (2.95–3.21) for current smoking, 1.48 (1.44–1.52) for BMI ≥ 30 kg/m 2, 1.11 (1.08–1.15) for HbA1c ≥ 58 mmol/mol (7.5%), 1.03 (1.00–1.06) for SBP ≥ 140 mmHg and 0.87 (0.84–0.90) for total cholesterol ≥ 5 mmol/l. Conclusions: Socio‐economic deprivation is associated with higher prevalence of smoking, BMI ≥ 30 kg/m 2 and HbA1c ≥ 58 mmol/mol (7.5%), and lower prevalence of total cholesterol ≥ 5 mmol/l among people with type 2 diabetes in Scotland. Effective approaches to reducing inequalities are required as well as reducing risk factor prevalence across the whole population. What's new?: Socio‐economic deprivation is associated with increased risk of cardiovascular disease in people with diabetes. This study, using a national database of quarter of a million people, found that socio‐economic deprivation is strongly positively associated with smoking and obesity, modestly positively associated with above‐target HbA1c, and modestly negatively associated with above‐target cholesterol, with no evidence of an association with above‐target blood pressure. Inequalities appear to have widened over time. Our findings may enable more effective interventions to reduce these inequalities by targeted approaches in subgroups of the population.